(3EYdGe GdgOi hYbjOI CQHGH GdJbis - (3GdSgQhQOj, CHh fUQ, YeQ Hf eMeO Hf YHO Gddg Hf eMeO Hf YHO Gddg, (B632 (3g`s ((3eMeO GdUaOjs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO GdPj QaY ZTGI GdZeI hHYO abO GdJeS efj hCfG eLGhQ HecI Gf GcJH dg YbjOI hSejJgG EYdGe GdgOis
(3BNQgG (B:s
(3hfYJbO hLhH GdLeYI hGdLeGYI hhLhH bVGA Mbhb GdeSdejf hGdGJaGb eYge Ydi eG GJabhG Ydjg hGfYbO ELeGYge ajg hdG fSJHOd QCjfG Ohf ELeGY GdeSdejfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5 / 62s
(3eYLe GdeDdajf (B2 / 575s
(3cTa GdXfhf (B2 / 1157s
(3TPQGJ GdPgH (B5 / 153s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds